Hepatitis C virus replication in hepatocellular carcinoma. Issue 9 (September 1995) - Niu, J; Kumar, U; Monjardino, J; Goldin, R; Rosin, D; Thomas, H C
Abstract : Hepatitis C virus (HCV) replication is reported in both tumour and non-tumour tissue in a case of hepatocellular carcinoma. Viral replication was established by showing the presence of minus strand HCV RNA by PCR amplification, after excluding residual reverse transcriptase activity of Taq polymerase. No minus strand was found in serum derived virion RNA. PCR amplified products from both tumour and non-tumour parenchyma were sequenced in the 5' non-coding region and shown to be identical. The genotype of this Indonesian patient was found to be 1b (or II), the most prevalent type in the Far East.